TCR ITAM multiplicity is required for the generation of follicular helper T-cells - Hwang, SuJin (Nat Commun, 2015)
The T-cell antigen receptor (TCR) complex contains 10 copies of a di-tyrosine Immunoreceptor-Tyrosine-based-Activation-Motif (ITAM) that initiates TCR signalling by recruiting protein tyrosine kinases. ITAM multiplicity amplifies TCR signals, but the importance of this capability for T-cell responses remains undefined. Most TCR ITAMs (6 of 10) are contributed by the CD3ζ subunits. We generated ‘knock-in' mice that express non-signalling CD3ζ chains in lieu of wild-type CD3ζ. Here we demonstrate that ITAM multiplicity is important for the development of innate-like T-cells and follicular helper T-cells, events that are known to require strong/sustained TCR–ligand interactions, but is not essential for ‘general' T-cell responses including proliferation and cytokine production or for the generation of a diverse antigen-reactive TCR repertoire.